Kualitas Pelayanan Publik Di Balai Pelayanan, Penempatan, Dan Perlindungan Tenaga Kerja Indonesia Wilayah Bandung - Setiawan, Wawan; Miharja, Sakrim; Lestari, Yeni Dewiyanti (Publica: Jurnal Pemikiran Administrasi Negara, 2019)
This study aims to analyze the quality of public services at the Bandung Service Center, Placement and Protection of Indonesian Workes (BP3TKI) Bandung. This research method uses  qualitative methods with descriptive approach. Data collection techniques used were in-depth interviews and documentation studies. Informants in this study were Head Of Correctional and Program Institution Section, Head of Placement Preparation Section, service staff and TKI. In addition, the steps in data analysis according to Miles and Huberman consist of three stages, namely: data reduction, data presentation and conclusion/ verification. The results of this study were obtained from the results of interviews that: (1) The quality of public service at the Indonesian Workforce Service, Placement and Protection Center (BP3TKI) Bandung has implemented five dimensions namely: Tangible, Reliability, Responsiviness, Assurance, Emphaty along with indicators. However, from some indicators there are still those that have not gone according to the wishes of Indonesian infrastructure, there are still officers who are capable and expert in operating the tools  available at BP3TKI Bandung, and the officers? inability to process service to TKI. (2) barriers that existin the implementation of public service at the Indonesian Workforce Service, Placement and Protection Center (BP3TKI) in Bandung is that there is no place for medical examinations for Indonesian migrant workers, and banks to pay for insurance so that migrant workers must leave the office, and for facilities and infrastructure that are still not maximal to support the service process.